A novel antibody-TCR (AbTCR) platform combines Fab-based antigen recognition with gamma/delta-TCR signaling to facilitate T-cell cytotoxicity with low cytokine release. Issue 1 (December 2018) - Xu, Yiyang; Yang, Zhiyuan; Horan, Lucas; Zhang, Pengbo; Liu, Lianxing; Zimdahl, Bryan; Green, Shon; Lu, Jingwei; Morales, Javier; Barrett, David; Grupp, Stephan; Chan, Vivien; et al.
Abstract The clinical use of genetically modified T-cell therapies has led to unprecedented response rates in leukemia and lymphoma patients treated with anti-CD19 chimeric antigen receptor (CAR)-T. Despite this clinical success, FDA-approved T-cell therapies are currently limited to B-cell malignancies, and challenges remain with managing cytokine-related toxicities. We have designed a novel antibody-T-cell receptor (AbTCR) platform where we combined the Fab domain of an antibody with the γ and δ chains of the TCR as the effector domain. We demonstrate the ability of anti-CD19-AbTCR-T cells to trigger antigen-specific cytokine production, degranulation, and killing of CD19-positive cancer cells in vitro and in xenograft mouse models. By using the same anti-CD19 binding moiety on an AbTCR compared to a CAR platform, we demonstrate that AbTCR activates cytotoxic T-cell responses with a similar dose-response as CD28/CD3ζ CAR, yet does so with less cytokine release and results in T cells with a less exhausted phenotype. Moreover, in comparative studies with the clinically validated CD137 (4-1BB)-based CAR, CTL019, our anti-CD19-AbTCR shows less cytokine release and comparable tumor inhibition in a patient-derived xenograft leukemia model.